Effect of the Harmonic Voltage Distortion on the Efficiency of a Compact Fluorescent Lamp - Rojas-Osorio, Esteban; Saavedra-Montes, Andrés Julián; Ramos-Paja, Carlos Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper evaluates the effect of the voltage harmonic distortion over the efficiency of a compact fluorescent lamp that is fed with a constant RMS voltage and constant frequency. Several works have been published about the assessment of compact fluorescent lamps, but the effect of the voltage distortion over the efficiency is still an open topic. This work focuses on designing an experiment to estimate the efficiency of a compact fluorescent lamp while changing the voltage harmonic distortion of the power supply. First, a mathematical model that represents a bus susceptible to harmonic distortion (high impedance) that feeds the compact fluorescent lamp is analyzed. Then the mathematical model is reproduced through a test bench in a laboratory of rotating electrical machines. The test bench produces a three-phase bus with constant voltage and frequency, and variable voltage harmonic distortion. The compact fluorescent lamp is subjected to varying harmonic voltage distortion while recording its electrical variables and the produced lumens to estimate its efficiency. That is a practical approach to calculate the lamp efficiency while several works limit their scope measuring only the efficiency of the input converter. The experimental results show that a variation of the voltage harmonic distortion of 8 % on a compact fluorescent lamp reduces its efficiency. Those results put into evidence the importance of regulating harmonic distortion limits to reduce or prevent the increment of power losses caused by harmonic components.